2023
DOI: 10.1021/acsami.3c03115
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Driven CoCr-LDH@VNiS2 as a Bifunctional Electrocatalyst for Overall Water Splitting and Flexible Supercapacitors

Abstract: Utilizing alternative energy sources to fossil fuels has remained a significant issue for humanity. In this context, efficient earth-abundant bifunctional catalysts for water splitting and energy storage technologies like hybrid supercapacitors have become essential for achieving a sustainable future. Herein, CoCr-LDH@VNiS 2 was synthesized by hydrothermal synthesis. The CoCr-LDH@VNiS 2 catalyst entails 1.62 V cell voltage to reach the current density of 10 mA cm −2 for overall water splitting. The CoCr-LDH@VN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The optimized energy level alignment caused by Co and introduced more active sites caused by its unique 3D bramble-like structure imported better structural stability with higher electronic transfer abilities and showed higher electrochemical activity. Importantly, the performance of NiCo 2 S 4 /NF catalyst was superior to some recently reported bifunctional electrocatalysts as shown in Figure d and furthermore certified that the NiCo 2 S 4 /NF catalyst had an excellent electroceutical ability.…”
Section: Results and Discussionsupporting
confidence: 65%
“…The optimized energy level alignment caused by Co and introduced more active sites caused by its unique 3D bramble-like structure imported better structural stability with higher electronic transfer abilities and showed higher electrochemical activity. Importantly, the performance of NiCo 2 S 4 /NF catalyst was superior to some recently reported bifunctional electrocatalysts as shown in Figure d and furthermore certified that the NiCo 2 S 4 /NF catalyst had an excellent electroceutical ability.…”
Section: Results and Discussionsupporting
confidence: 65%
“…On the other hand, various Ni-based materials, especially NiX (X = O, S, Se, P, etc. ), have shown promising electrocatalytic performance toward the water-splitting reaction. , Among these, NiO is preferred in terms of ease of preparation and moderate activity. Although it has optimal active sites on the surface for the adsorption of hydroxide and various intermediates, it possesses a very low electrochemically active surface area, which results in poor mass transfer properties.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al synthesized petal-like nickel–aluminum LDH and demonstrated excellent performance of supercapacitor. However, the full potential of LDH performance has not been exploited, which derives from poor conductivity, structure agglomeration, and undermining. , To tackle these challenges, researchers have proposed various approaches, including interlayer engineering, defect engineering, heterostructure engineering, and ternary engineering by introducing a third transition metal element to improve the material’s structure. In these studies, in situ growth on a current collector presents a more promising strategy. Chen et al constructed the in situ growth of cobalt–nickel LDH nanosheets on the nickel foam with a growth promoter of hexadecyltrimethylammonium bromide.…”
Section: Introductionmentioning
confidence: 99%